Optimal starting block configuration in sprint running: A comparison of biological and prosthetic legs - Taboga, P.; Grabowski, A. M.; Di Prampero, P. E.; Kram, R. (Journal of Applied Biomechanics, 2014)
In the 2012 Paralympic 100 m and 200 m finals, 86% of athletes with a unilateral amputation placed their unaffected leg on the front starting block. Can this preference be explained biomechanically? We measured the biomechanical effects of starting block configuration for seven nonamputee sprinters and nine athletes with a unilateral amputation. Each subject performed six starts, alternating between their usual and unusual starting block configurations. When sprinters with an amputation placed their unaffected leg on the front block, they developed 6% greater mean resultant combined force compared with the opposite configuration (1.38 ± 0.06 vs 1.30 ± 0.11 BW, P = .015). However, because of a more vertical push angle, horizontal acceleration performance was equivalent between starting block configurations. We then used force data from each sprinter with an amputation to calculate the hypothetical starting mechanics for a virtual nonamputee (two unaffected legs) and a virtual bilateral amputee (two affected legs). Accelerations of virtual bilateral amputees were 15% slower compared with athletes with a unilateral amputation, which in turn were 11% slower than virtual nonamputees. Our biomechanical data do not explain the starting block configuration preference but they do explain the starting performance differences observed between nonamputee athletes and those with leg amputations.